Um novo estimador exponencial por partes da curva de sobrevivência: um estudo comparativo - Moraes, Fabíola Eugênio Arrabaça (2006)
In this work we revise the main basic concepts on survival analysis and reliability. We present the most known nonparametric estimators of the survival function in the presence of censured data. Their estimates are calculed and compared in an real data set on human renal transplants. We point some problems that are not usually considered in the structure of these estimators. As consequense of such problems we can observe possible distortions in the estimates the direction of sub or over estimating the main characteristics of interest. Some alternatives are pointed out for finding lesse vulnerable estimators. Moreover, we propose a new modified piece wise exponential estimator, pointing out its properties.